ANALISIS HUBUNGAN PERENCANAAN DAN PARTISIPASI MASYARAKAT DENGAN EFEKTIVITAS PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) - Dierla Vietha Tryuni Saputrie; Augustin Rina Herawati; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The lack of 100% access to drinking water and proper sanitation through the PAMSIMAS program is known to be caused by several factors, including planning and community participation. This research aims to determine : (1) describe the variables of program effectiveness (Y), planning (X1), and community participation (X2), (2) the relationship between planning on the effectiveness of PAMSIMAS program, (3) the relationship between community participation on the effectiveness of PAMSIMAS program, (4) the relationship between planning and community participation on the effectiveness of PAMSIMAS program in Ringinanom Village, Parakan District, Temanggung Regency. This type of research is quantitative explanatory. The number of samples are 102 respondents. Data collection techniques using questionnaires, interviews, documentation and observation. Data analysis technique to test the hypothesis using the Kendall Tau correlation coefficient, Kendall concordance coefficient, and the coefficient of determination. The results show that : (1) the variables are classified as good with the program effectiveness value of 3.11, (2) there is a relationship between planning and the effectiveness of PAMSIMAS program with a contribution value of 17,6%, (3) there is a relationship between community participation and the effectiveness of PAMSIMAS program with a contribution value of 74,3%, (4) there was a relationship between planning and community participation on the effectiveness of PAMSIMAS program with a contribution value of 75,2%. Based on that result, to achieve program effectiveness it is necessasy to improve the community’s competence and public awareness to be actively involved in the program.